Identification of C/EBPα as a novel target of the HPV8 E6 protein regulating miR-203 in human keratinocytes. - Anna M Marthaler; Marta Podgorska; Pascal Feld; Alina Fingerle; Katrin Knerr-Rupp; Friedrich Grässer; Hans Smola; Klaus Roemer; Elke Ebert; Yoo-Jin Kim; Rainer M Bohle; Cornelia S L Müller; et al. (PLoS Pathogens)
Patients suffering from Epidermodysplasia verruciformis (EV), a rare inherited skin disease, display a particular susceptibility to persistent infection with cutaneous genus beta-human papillomavirus (beta-HPV), such as HPV type 8. They have a high risk to develop non-melanoma skin cancer at sun-exposed sites. In various models evidence is emerging that cutaneous HPV E6 proteins disturb epidermal homeostasis and support carcinogenesis, however, the underlying mechanisms are not fully understood as yet. In this study we demonstrate that microRNA-203 (miR-203), a key regulator of epidermal proliferation and differentiation, is strongly down-regulated in HPV8-positive EV-lesions. We provide evidence that CCAAT/enhancer-binding protein α (C/EBPα), a differentiation-regulating transcription factor and suppressor of UV-induced skin carcinogenesis, directly binds the miR-203 gene within its hairpin region and thereby induces miR-203 transcription. Our data further demonstrate that the HPV8 E6 protein significantly suppresses this novel C/EBPα/mir-203-pathway. As a consequence, the miR-203 target ΔNp63α, a proliferation-inducing transcription factor, is up-regulated, while the differentiation factor involucrin is suppressed. HPV8 E6 specifically down-regulates C/EBPα but not C/EBPβ expression at the transcriptional level. As shown in knock-down experiments, C/EBPα is regulated by the acetyltransferase p300, a well-described target of cutaneous E6 proteins. Notably, p300 bound significantly less to the C/EBPα regulatory region in HPV8 E6 expressing keratinocytes than in control cells as demonstrated by chromatin immunoprecipitation. In situ analysis confirmed congruent suprabasal expression patterns of C/EBPα and miR-203 in non-lesional skin of EV-patients. In HPV8-positive EV-lesions both factors are potently down-regulated in vivo further supporting our in vitro data. In conclusion our study has unraveled a novel p300/C/EBPα/mir-203-dependent mechanism, by which the cutaneous HPV8 E6 protein may expand p63-positive cells in the epidermis of EV-patients and disturbs fundamental keratinocyte functions. This may drive HPV-mediated pathogenesis and may potentially also pave the way for skin carcinogenesis in EV-patients.